PENGARUH KEDISIPLINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT RnR A INDONESIA KOTA BEKASI - Raffi, Hafidz Dwi (PT Naureen Digital Education, 2023)
Work discipline is an intuitive individual initiative following all the rules determined by the organization and various applicable social norms. Work discipline can be seen from the level of attendance, work procedures, commitment to superiors, work awareness and responsibility. Supervision is the act of monitoring the activities of an intuitive organization to ensure that every work proceeds in accordance with the plans that have been set. The expert's objective in carrying out this research is the intuitive knowledge of the influence of discipline and motivation on the performance of employees of PT RnR A INDONESIA Beikasi City, both partially and simultaneously. The method used in this research is quantitative research method with data collection techniques using questionnaires. Data analysis techniques use the classical assumption test, multiple linear regression, t test, F test, and coefficient of determination. Data processing in this research uses SPSS (Statistics Package for Social Sciences) software. The population size in this research is 100 people and the sample size is 103 people. The sampling technique in this research uses random sampling technique using Ruimuis Slovin. The results of this research indicate that work discipline has a significant impact on work effectiveness. Partially, work supervision also has a significant impact on work effectiveness. Simultaneously, discipline and motivation have a significant impact on employee performance.